Utility of Three Adiposity Indices for Identifying Left Ventricular Hypertrophy and Geometric Remodeling in Chinese Children - Wang, Huan; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Endocrinology, 2021)
Background: Previous studies have shown that waist-to-height ratio (WHtR) performed similarly well when compared to body mass index (BMI) and waist circumference (WC) for identifying cardiovascular risk factors. However, to our knowledge, the performance of these three adiposity indices for identifying left ventricular hypertrophy (LVH) and left ventricular geometric (LVG) remodeling in youth has not been assessed. We aimed to determine the utility of BMI, WC and WHtR for identifying LVH and LVG in Chinese children. Methods: This study included 1,492 Chinese children aged 6-11 years. Adiposity indices assessed were BMI, WC and WHtR. LVH and high relative wall thickness (RWT) were defined using sex- and age-specific 90th percentile values of left ventricular mass index and RWT, respectively, based on the current population. LVG remodeling included concentric remodeling (CR), eccentric hypertrophy (EH) and concentric hypertrophy (CH), which was defined based on the combination of LVH and high RWT. Results: The magnitude of association of central obesity defined by WHtR with LVH (odds ratio [OR] =10.09, 95% confidence interval [CI] =6.66-15.29) was similar with general obesity defined by BMI (OR=10.49, 95% CI=6.97-15.80), and both were higher than central obesity defined by WC (OR=6.87, 95% CI=4.57-10.33). Compared with BMI, WHtR had better or similar predictive utility for identifying LVH, EH, and CH (the area under the curve [AUC]: 0.84 vs. 0.79; 0.84 vs. 0.77; 0.87 vs. 0.88, respectively); WC had worse or similar discriminatory utility with AUCs of 0.73, 0.70, 0.83, respectively. Conclusion: WHtR performed similarly or better than BMI or WC for identifying LVH and LVG remodeling among Chinese children. WHtR provides a simple and convenient measure of central obesity that might improve the discrimination of children with cardiac structural damage.